Shaping future entrepreneurs: Assessing business pitching skills / Farhana Fakhira Ismail and Dr. Gurmeet Kaur Surindar Singh - Ismail, Farhana Fakhira; Surindar Singh, Gurmeet Kaur (Faculty of Pharmacy, 2023)
On July 13, 2023, final-year students of the Bachelor of Pharmacy (PH240) at UiTM Puncak Alam participated in a significant event that marked a pivotal moment in their educational journey. This event was the business pitching assessment for the PHC693 Entrepreneurship in Pharmacy course. Designed with the intention of nurturing students' entrepreneurial skills and fostering their innovative thinking in the realm of community pharmacy, this assessment held a paramount place in their academic journey. The organisers took a unique approach to amplify the impact of this assessment by inviting esteemed community pharmacists, individuals who are also business owners, to join forces with the faculty lecturers, particularly those from the Department of Clinical Pharmacy, as assessors.